Panel selection and training in the sensory analysis of coffee Coffea Arabica L. - Gutiérrez G., Nelson; Barrera B., Oscar Mauricio (Revista de Ciencias Agrícolas, 2015)
The purpose of this paper was to define a panel training methodology in the sensory evaluation of specialty coffees using the Specialty Coffee Association of America (SCAA) methodology. The training process included selection, motivation, theoretical support, basic tests in flavor and aroma, and specific tests in the descriptive analysis of coffee samples. The training time was three months. Twenty one coffee samples were evaluated in three sessions of four hours each; “t” Student tests and cluster analysis were carried out to evaluate the effectiveness of the training methodology. The results showed that after the third training session, corresponding to 12 hours in the stage of specific training, no statistically significant differences (p>0,05) were found between the judgments given by expert panel and the panel in training process; the dispersion diagrams from the cluster analysis proved the effectiveness of the training methodology.